Farligt gods inom hamnområden - Finns det en klar gräns mellan regelverken ADR-S, RID-S samt IMDG-koden? - Lindberg, Anna; Simonsson, Linnéa (My University, 2017)
Port areas are a meeting place for different modes of transport which are road, sea and railway. These transports can in some cases contain dangerous goods, and therefore different regulations apply depending on the mode of transport. In Sweden, ADR-S is applied on road transport, RID-S on railway and the IMDG-code with sea transports. In port areas, all these three regulations intersect and are all applicable but have different rules that overlap each other. Therefore, it is interesting to investigate where the interface between these regulations go, which has been done through a survey of how the regulations has been applied in Swedish ports today. The aim of this report is to examine where the interface between the three different regulations are within a port area with focus on how the ports work today. The report consists of three questions based on the aim of the report. The questions have been answered by using two methods, interview and questionnaires, to get qualitative data. An interview was done with the Swedish coast guard which have supervision of dangerous goods in port areas and the questionnaires was sent out to eleven different ports and their safety advisers. The questions both in the interview and questionnaires were based on the three main questions in the report. The replies gathered from the ports and the interview is presented in the result section of the report to then be discussed in the discussion section. After an analysis of the different replies the conclusion was that there is no specific border between the different regulations ADR-S, RID-S and the IMDG-code. However, the Swedish coast guard have a specific idea of where the borders go. The author’s recommendation is therefore that the ports should apply the interface in the same way as the Swedish coast guard has.
Keywords: Transport; Transportteknik och logistik; Transport; Transport Systems and Logistics